A multicomponent reaction platform towards multimodal near-infrared BODIPY dyes for STED and fluorescence lifetime imaging. Issue 10 (1st September 2022) - Fernandez, Antonio; Kielland, Nicola; Makda, Ashraff; Carragher, Neil O.; González-García, M. Carmen; Espinar-Barranco, Laura; González-Vera, Juan A.; Orte, Angel; Lavilla, Rodolfo; Vendrell, Marc
Abstract : By combining synthetic multicomponent reactions and cell-based screenings, we identified NIRBD-62c as a multimodal probe for STED and fluorescence lifetime imaging of the vesicular traffic between intracellular compartments and the plasma membrane. Abstract : We report a platform combining multicomponent reaction synthesis and automated cell-based screening to develop biocompatible NIR-BODIPY fluorophores. From a library of over 60 fluorophores, we optimised compound NIRBD-62c as a multimodal probe with suitable properties for STED super-resolution and fluorescence lifetime imaging. Furthermore, we employed NIRBD-62c for imaging trafficking inside cells and to examine how pharmacological inhibitors can alter the vesicular traffic between intracellular compartments and the plasma membrane.